2021
DOI: 10.1080/21655979.2021.1944027
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of DNA polymerase ζ relieved the chemoresistance of glioma via inhibiting the PI3K/AKT signaling pathway

Abstract: Previous reports suggest that DNA polymerase ζ is highly expressed in glioma tissues. The present study aimed to investigate the roles of the REV7 subunit of DNA polymerase ζ in glioma cell chemoresistance and its underlying mechanisms. The bioinformatics method was used to compare the expression of REV7 in glioma and normal tissues. The expression of REV7 in glioma tumor samples and the adjacent tissue was examined by reverse transcription polymerase chain reaction. Moreover, an in vitro analysis using glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Although REV7 expression is low in most normal human tissues except for the testis, its expression is relatively high in various human tumor tissues, including colon, ovarian, breast, esophageal, lung, and skin cancers, gliomas, diffuse large B cell lymphomas, and testicular germ cell tumors (TGCTs) [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. REV7 expression levels are correlated with cell proliferation ability represented by Ki-67 labeling indexes in small cell lung carcinomas and malignant melanomas, with metastases in breast and lung cancers, with tumor thickness in malignant melanomas, and with tumor sizes of gliomas [ 89 , 92 , 93 , 94 , 95 ]. There is a significant association between high levels of REV7 expression and poor prognosis in several tumors, including colon, breast, lung, gastric, and advanced ovarian cancers, diffuse large B cell lymphomas, and advanced bone and soft tissue sarcomas, suggesting the utility of REV7 as a biomarker for cancer prognosis [ 85 , 87 , 88 , 89 , 94 , 96 , 97 ].…”
Section: Rev7 In Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Although REV7 expression is low in most normal human tissues except for the testis, its expression is relatively high in various human tumor tissues, including colon, ovarian, breast, esophageal, lung, and skin cancers, gliomas, diffuse large B cell lymphomas, and testicular germ cell tumors (TGCTs) [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. REV7 expression levels are correlated with cell proliferation ability represented by Ki-67 labeling indexes in small cell lung carcinomas and malignant melanomas, with metastases in breast and lung cancers, with tumor thickness in malignant melanomas, and with tumor sizes of gliomas [ 89 , 92 , 93 , 94 , 95 ]. There is a significant association between high levels of REV7 expression and poor prognosis in several tumors, including colon, breast, lung, gastric, and advanced ovarian cancers, diffuse large B cell lymphomas, and advanced bone and soft tissue sarcomas, suggesting the utility of REV7 as a biomarker for cancer prognosis [ 85 , 87 , 88 , 89 , 94 , 96 , 97 ].…”
Section: Rev7 In Cancermentioning
confidence: 99%
“…The mechanisms for the upregulation of REV7 in tumor tissues have not been fully elucidated, although zinc finger protein with KRAB and SCAN domains 3 (ZKSCAN3), an oncogenic transcription factor, acts as a transcriptional repressor of REV7 in cultured tumor cells [ 98 ]. The contribution of REV7 to poor prognosis in various malignancies may be explained by the following: (1) REV7-high tumors exhibit the potential for high proliferation and tend to be more advanced [ 89 , 92 , 93 , 94 , 95 ]; and (2) REV7 expression affects cell mobility, intracellular signaling, EMT, and sensitivity to chemoradiotherapy, which will be discussed later. In support of this, a clinical study on advanced bone and soft tissue sarcomas demonstrated that REV7 expression is significantly high in non-responders to trabectedin and olaparib combination therapy [ 97 ].…”
Section: Rev7 In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, miRNAs, which are small ncRNAs that bind to the 3' untranslated region of target mRNAs to modulate gene expression, could regulate endothelial function, in ammation, and vascular remodeling in hypertensive retinopathy [7][8][9]. Similarly, lncRNAs that are longer than 200 nucleotides and could modulate gene expression through various mechanisms, have been shown to be differentially expressed within the retinas of hypertensive rats and may contribute to the pathogenesis of hypertensive retinopathy [10,11]. Furthermore, circRNAs, which are covalently closed circular RNAs that act as miRNA sponges, have recently been identi ed as potential regulators of gene expression in hypertensive retinopathy [12,13].…”
mentioning
confidence: 99%